STRATEGI KEPEMIMPINAN PENDIDIKAN DALAM MENGATASI PROBLEMATIKA KEARSIPAN BERBASIS DIGITAL DI LEMBAGA PENDIDIKAN - Sulia Fitri Hasanah; Friska Amalia; Zufar Ramiro Razan; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze educational leadership strategies in addressing problems related to digital-based archival systems in educational institutions. Digital transformation in educational administration requires an effective, efficient, and integrated archival system. However, challenges such as low digital literacy, limited infrastructure, and suboptimal policies remain major obstacles. This research uses a library research method by reviewing various sources such as books, scientific journals, and relevant documents. The findings indicate that adaptive, innovative, and technology-based educational leadership plays a crucial role in improving the effectiveness of digital archive management. The strategies include strengthening digitalization policies, enhancing human resource competencies, and optimizing the use of information technology. Therefore, educational leadership becomes a key factor in realizing a modern and accountable digital archival system. Keywords: educational leadership, digital archives, digital transformation, educational management